Geocultural Landscape and Sustainable Development at Apano Meria in Syros Island, Central Aegean Sea, Greece: An Ecomuseological Approach for the Promotion of Geological Heritage - Tsipra, Theodora; Hara Drinia (Heritage, 2022)
In order to create a cultural landscape, the number of different types of ecomuseums around the world, covering many sites, has recently increased. Their establishment aims at the protection of natural and cultural resources. The north area of Syros Island offers significant opportunities for the development of a museum model that promotes the sustainable development of the local community. The aim of this study is to investigate the feasibility of developing a museum model that promotes the sustainable development of the local community in Apano Meria, Syros Island, which is a representative site with natural, geological, and archaeological heritage. For this purpose, the engagement and participation of the local inhabitants was evaluated through various activities, the basic principles of which are based on the concepts of New Museology and, more specifically, those of ecomuseums. Qualitative research was carried out through on-site observations, including discussions, participant observation, documentation, and in-depth interviews with local people. This research revealed that, so far, the conservation of the Apano Meria landscape is mainly due to the action of local people, who have repeatedly been called upon to show strong resistance to external factors that threatened to alter it. In their long-term effort to preserve and protect the area, but also to develop it in terms of sustainable development, the idea of its possible future inclusion in the UNESCO Global Network of Geoparks was proposed.